The Political Gap in Nepal’s Child Protection - Rathour, Sushil Singh (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Children’s Act 2075 and constitutional protections are examples of Nepal’s progressive legal development; however, the implementation of these directives is still uneven. Political parties are the main policy makers in Nepal’s federal system, but little is known about how they specifically prioritize child protection. The gap between political rhetoric and actual legislative and budgetary results is examined in this study. Objective: The "political gap" the discrepancy between the actual legislative and budgetary results at the federal and local levels and the child rights promises found in political party rhetoric is the subject of this study. It especially looks at how the effectiveness of child protection systems is impacted by important political actors’ preference for physical infrastructure over social protection. Methods: Systematic Document Analysis is the focal point of the study’s qualitative research design. The data corpus is divided into three categories: (1) National legislative frameworks and the Children’s Act (2075); (2) Federal Election Manifestos of the CPN-UML and Nepali Congress (2017 and 2022); and (3) institutional performance reports and budget briefs from international organizations and the National Child Rights Council (2021–2026). Thematic content analysis was used to examine data to compare political rhetoric with practical results. Results: The results show that local political concerns centered on physical infrastructure often overshadow major parties’ high symbolic commitment to child rights in their manifestos. Less than 30% of municipalities have sufficiently funded child protection committees, according to analysis. Additionally, party-affiliated groups are still politicizing classrooms, which is against the rules of "Schools as Zones of Peace" (SZOP). Conclusion: The "political gap" is the main barrier to child welfare in Nepal, according to the study’s findings. The legislative frameworks will remain mainly ineffectual at the grassroots level until there is a bipartisan agreement to approach child safety as a primary political priority rather than a secondary social issue. Novelty: This study goes beyond conventional legal analysis to analyze the "political will" that propels or impedes the implementation of human rights in Nepal, offering a distinctive critique of child rights via the perspective of political party accountability and federal budget prioritizing.